2023
DOI: 10.1007/s11262-023-01981-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and phylogenetic analysis of bovine gammaherpesvirus 4 isolated in China, 2022

Abstract: Bovine gammaherpesvirus 4 (BoHV-4) is a common virus detected in bovine with respiratory disease worldwide. In this study, we identified and characterized a novel BoHV-4 strain, referred as HB-ZJK, in vaginal swabs collected from cattle in China, 2022. The long unique region (LUR) of HB-ZJK is 10,9811 bp in length. It shares 99.17% to 99.38% nucleotide identity to five BoHV-4 strains available in GenBank and the highest similarity was seen with BoHV-4V. test (JN133502.1) strain (99.38%). Mutations, insertions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The two genome sequences reported in this study add significantly to the six BoGHV4 genomes previously described [7,15,[27][28][29]. Both Argentinean isolates presented the highest nt p-distance values, indicating a greater level of divergence.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The two genome sequences reported in this study add significantly to the six BoGHV4 genomes previously described [7,15,[27][28][29]. Both Argentinean isolates presented the highest nt p-distance values, indicating a greater level of divergence.…”
Section: Discussionsupporting
confidence: 53%
“…Partial nt sequences of gB and TK have been widely used for BoGHV4 classification and diagnostic purposes [17,18,21,29,30,37,63]. The phylogenetic comparison showed that TK sequences displayed the most similar tree and the shortest geodesic distance compared to the CG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype-3 viruses are African buffalo strains [ 7 ]. Six complete genomes of genotype-1 BoHV-4 strains have been sequenced to date, including 66-p-347, SD16-38, and SD16-49 from the United States [ 2 , 32 ]; V.test from Belgium [ 25 ]; FMV09 from Canada [ 14 ]; and HB-ZJK from China [ 15 ].…”
mentioning
confidence: 99%
“…Two BoHV-4 strains of undetermined genotype, including K1 and Taiwan, have been isolated from cattle with leukosis and bovine arterial endothelial cell cultures in Taiwan [ 21 , 23 ]. Recently, four strains of genotype 1, including 512, BL6010, J4034, and HB-ZJK, have been isolated from cattle in China [ 15 , 22 ]. Strain 512 was serendipitously isolated from buffy coat fractions of a calf during attempts to isolate the bovine viral diarrhea virus (BVDV).…”
mentioning
confidence: 99%